Promises of Main Group Metal–Based Nanostructured Materials for Electrochemical CO2 Reduction to Formate - Han, Na; Ding, Pan; He, Le; Li, Youyong; Li, Yanguang (Advanced energy materials, 2020)
Selective CO2 reduction to formic acid or formate is the most technologically and economically viable approach to realize electrochemical CO2 valorization. Main group metal–based (Sn, Bi, In, Pb, and Sb) nanostructured materials hold great promise, but are still confronted with several challenges. Here, the current status, challenges, and future opportunities of main group metal–based nanostructured materials for electrochemical CO2 reduction to formate are reviewed. Firstly, the fundamentals of electrochemical CO2 reduction are presented, including the technoeconomic viability of different products, possible reaction pathways, standard experimental procedure, and performance figures of merit. This is then followed by detailed discussions about different types of main group metal–based electrocatalyst materials, with an emphasis on underlying material design principles for promoting the reaction activity, selectivity, and stability. Subsequently, recent efforts on flow cells and membrane electrode assembly cells are reviewed so as to promote the current density as well as mechanistic studies using in situ characterization techniques. To conclude a short perspective is offered about the future opportunities and directions of this exciting field. Main group metal–based nanostructured materials hold great potential for electrochemical CO2 reduction to formate. Here, their current status and challenges are reviewed with an emphasis on underlying material design principles for promoting the reaction activity, selectivity, and stability. A short perspective is also offered about the future opportunities and directions of this exciting field.